Estudio de la flora muscinal del hayedo de Montejo de la Sierra (provincia de Madrid) - Galiano, Emilio F.; Blanco Castro, Emilio; Ron Álvarez, María Eugenia; Fuertes Lasala, Esther (Botanica Complutensis, 1982)
Sin resumen